If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 60 = 5x + -60 Reorder the terms: 60 + 2x = 5x + -60 Reorder the terms: 60 + 2x = -60 + 5x Solving 60 + 2x = -60 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 60 + 2x + -5x = -60 + 5x + -5x Combine like terms: 2x + -5x = -3x 60 + -3x = -60 + 5x + -5x Combine like terms: 5x + -5x = 0 60 + -3x = -60 + 0 60 + -3x = -60 Add '-60' to each side of the equation. 60 + -60 + -3x = -60 + -60 Combine like terms: 60 + -60 = 0 0 + -3x = -60 + -60 -3x = -60 + -60 Combine like terms: -60 + -60 = -120 -3x = -120 Divide each side by '-3'. x = 40 Simplifying x = 40
| z=3x+4y^2 | | (-20)-(-4m)=(-5m)-(-15) | | -9=-77+x | | U(3U+4)= | | 2x+60+5x-60=180 | | -20-(-4m)=(-5m)-(-15) | | -8b=2 | | 6x=13x-6 | | (6+w)(5w-1)=0 | | 87=94-n | | -14=-1-2v | | -5=x-1+1 | | 4-m=14 | | 1/s^.75=1/2 | | -4=3m+n | | 8x^2-80x+168=0 | | 6=4.50 | | 5x^2-17x-40=(5x+8) | | 8=-4n-4n | | 5v-v=-4 | | -11.6w=-10.8w+15.36 | | 42+y-2y(7)=0 | | d+-729=130 | | 4m+7=-13 | | -8=4p-8p | | 7+3y=-21 | | 8x-6w+3x+7y+2y+2w= | | 3p+4(p-2)=44.50 | | -16f+12=-20f | | y=6.5x-4 | | 3(2x-4)=6(x+s) | | 6p+7q+8p-4q-2p= |